Mozambique Energy Sector Policy Note - World Bank (Washington, DC, 2016)
This Energy Sector Policy Note is intended to support the Government of Mozambique in determining priorities for policy decisions with the aim of delivering efficiently produced, technically and financially sustainable electricity supply to the Mozambican population. To support the development of recommendations, this Note includes simulation analysis based on the current finances of the sector. Electricidade de Macambique’s (EDM) corporate financial model was adapted for this work. Targets for electrification are based on discussions with government officials. EDM’s current generation pipeline and its timing was taken as a given in order to simulate investment needs and evolution of sector finances under various tariff and funding availability assumptions. The various simulations and the broader sector quantitative and qualitative discussion should support policy formulation and prioritization going forward. The power sector in Mozambique faces three key challenges: i) to provide reliable and efficient electricity supply to its customers; ii) to cope with the increase in the electricity demand from its current (and future) customer base by expanding its generation and transmission capacity; and, iii) to provide access to electricity to the vast majority of the population. The importance of the timing of new generation to export power to South Africa also points to the importance of the backbone transmission project to evacuate the power from the center of the country – thereby enabling exports. Increasing access in line with Government targets will require major investments. The Government needs to consider the trade-offs between the ambition of the access targets imposed upon EDM and the sector’s broader financial viability for carrying out operations, maintenance and investment. Relaxation of the access target so that the 50 percent target is achieved by 2030 instead of 2023 gives EDM more liquidity in the first years.